On the DMT of RF energy harvesting-based dynamic decode-and-forward relaying - Rao, Yepuri Sudhakara (2020)
A multiple relay-based system, where all the relay nodes powered by radio frequency-based energy harvesting (EH), is considered. The present letter characterizes the diversity-multiplexing tradeoff (DMT) for EH-based dynamic decode-and-forward (EH-DDF) protocol for independent quasi-static Rayleigh faded channels. It is shown that the achievable diversity gain of EH-DDF improves with the reduction in the EH intervals. However, it is observed that the performance difference exists between classical DDF and EH-DDF even for infinitesimal harvest duration in lower multiplexing gain region.